Receptor-Type Guanylyl Cyclase at 76C (Gyc76C) Regulates De Novo Lumen Formation during Drosophila Tracheal Development. - Monn Monn Myat; Unisha Patel (PLoS ONE, 2016)
Lumen formation and maintenance are important for the development and function of essential organs such as the lung, kidney and vasculature. In the Drosophila embryonic trachea, lumena form de novo to connect the different tracheal branches into an interconnected network of tubes. Here, we identify a novel role for the receptor type guanylyl cyclase at 76C (Gyc76C) in de novo lumen formation in the Drosophila trachea. We show that in embryos mutant for gyc76C or its downsteam effector protein kinase G (PKG) 1, tracheal lumena are disconnected. Dorsal trunk (DT) cells of gyc76C mutant embryos migrate to contact each other and complete the initial steps of lumen formation, such as the accumulation of E-cadherin (E-cad) and formation of an actin track at the site of lumen formation. However, the actin track and E-cad contact site of gyc76C mutant embryos did not mature to become a new lumen and DT lumena did not fuse. We also observed failure of the luminal protein Vermiform to be secreted into the site of new lumen formation in gyc76C mutant trachea. These DT lumen formation defects were accompanied by altered localization of the Arf-like 3 GTPase (Arl3), a known regulator of vesicle-vesicle and vesicle-membrane fusion. In addition to the DT lumen defect, lumena of gyc76C mutant terminal cells were shorter compared to wild-type cells. These studies show that Gyc76C and downstream PKG-dependent signaling regulate de novo lumen formation in the tracheal DT and terminal cells, most likely by affecting Arl3-mediated luminal secretion.